Le régime alimentaire des Gorilles de plaine de l’Est, Gorilla beringei graueri et la pharmacopée humaine : Alimentation ou automédication ? - Dalley-Divin Kambale Saa-Sita; Shelly Masi; Aimée Lorela Katungu Sawa-Sawa; Jean-Claude Kyungu Kasolene; Jean Malekani Mukulire (Revue de Primatologie)
Humans share with great apes many diseases but also, locally, the use of food or medicinal plants. The present study aims to document the diet of the wild eastern lowland gorillas (Gorilla beringei graueri), still very less studied, and to relate it to the human pharmacopoeia. From February to June 2016, observations on the feeding activity of two groups of eastern lowland gorillas (Nindividuals=6) at Mount Tshiabirimu in Virunga National Park (Lubero Territory, North Kivu Province, Democratic Republic of Congo) were obtained by continuous focal sampling. After conducting an ethno-pharmacological survey among the local population (167 interviewees), we identified 15 plant species representing 12 botanical families, which are part of the gorilla diet and are also used by the local population in the treatment of various diseases. Chemical, biological and pharmacological properties of those plants could be likely to help great apes healing from different bacteria, viruses and other pathogens. Given both the phylogenetic proximity of great apes and humans and the small proportion of wild plant species known by humans in the tropical forest, the observation of the diet of a species of great apes still very less known, such as the gorillas of the East, could lead to the discovery of new plants that may be useful for human health.